2020
DOI: 10.1002/apj.2498
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the evolution of damage and permeability of coal containing gas based on acoustic emission characteristics

Abstract: The gas permeability of a coal seam was the main factor determining the efficiency of gas extraction from the mines and was closely related to the coal damages. In this paper, a triaxial compression failure test of the raw coal was carried out in the gas seepage state using the MTS 815 rock mechanics testing system. The damage evolution law of the coal containing gas under triaxial compression was studied based on acoustic emission characteristics. The damage evolution parameters were determined using acoustic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Based on the evolution of the fatigue damage variable of coal-rock mass under the action of cyclic loading, Xiao [37] proposed a time-dependent damage variable and derived the damage constitutive model under the action of cyclic loading. Liu et al [38] found that the gas permeability of coal seam was the main factor that determines the efficiency of gas extraction in mines. It was closely related to coal damage.…”
Section: Geofluidsmentioning
confidence: 99%
“…Based on the evolution of the fatigue damage variable of coal-rock mass under the action of cyclic loading, Xiao [37] proposed a time-dependent damage variable and derived the damage constitutive model under the action of cyclic loading. Liu et al [38] found that the gas permeability of coal seam was the main factor that determines the efficiency of gas extraction in mines. It was closely related to coal damage.…”
Section: Geofluidsmentioning
confidence: 99%